Horrid Henry and the mega-mean time machine - Simon, Francesca; Ross, Tony (Naperville, Ill. : Sourcebooks Jabberwocky, 2009)
Contains four stories that feature Horrid Harry, and features the title selection in which Horrid Harry sends his brother, Perfect Peter, into the future with the time machine he built himself, but the future is not quite what Peter had hoped.
Originally published: Great Britain : Orion Children's Books, 2005.
Bulletin (Center for Children's books).
School Library Journal.
Bulletin (Center for Children's books), June 2009.
School Library Journal, April 2009.
3.0
Keywords: Human behavior -- Juvenile fiction; Behavior -- Fiction; Human behavior -- Fiction